Sociology in times of glocalization - Karner, Christian (Anthem Press, 2023)
This book offers a series of critical discussions of how sociology is responding to the challenges of globalization, to local counter-reactions to them, to the many ways 'the global' impacts our lives, and to the new questions about research this poses.